Comparing the Tasks of Two English Textbooks - Endah Woro Hapsari; Dwi Riyanti; Ikhsanudin Ikhsanudin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2019)
The purpose of this article is to compare two English textbooks on the tenth-grade level. They were official books published by Goverment of Indonesia (GOI) published in 2014 and 2017. Littlejohn’S framework was applied to analyzing the process. The evaluation covers objective description, subjective analysis and subjective inference. Yet, this article focused on objective description and subjective analysis. The result found that there was significant revision in those books. It could be seen on the analysis result. This research analyzed elevent points- place of the learner’s material in any wider set of materials, published form of the learner’s materials, subdivision of the learner’s materials into sections, subdivision of sections into sub-sections, continuity, route, access, aims, principle of selection, pronciple of sequencing and subject matter and focus on subject matter. Based on elevent analyzing point, five of them was revised by the book author. The revision lied on subdivision on learners' materials, a subdivision of section into subsections, and access-publication section. Furthermore, on the design part, the revision lied on the aims and the objectives of books. In addition, the later book has better design than the previous one. The learning objectives are clearly stated on the preface part and it designed through the understandable task instructions.